The Effect of Participation of Girl Students on Consumption of Fruit and Vegetable in Family - Tahereh Gholipour; Monireh Anoosheh; Fazlollah Ahmadi (Iran University of Medical Sciences, 2008)
Background and Aim: Fruits and vegetables are essential part of healthy diets. Increasing evidence indicates that they may help to prevent major diseases such as heart diseases, some types of cancers, type 2 diabetes mellitus, stroke and etc. The aim of the study was to investigate the effect of girl students' participation on consumption of fruit and vegetables in the family.   Materials and Methods: This study had a quasi-experimental research design with two groups (experimental and control) and was carried out in 10 middle- schools in Tabriz during the year 2006. A number of 200 students participated in this study. The students in the experimental group (n=100) taught to research objectives (healthy diets, fruit and vegetable consumption, the methods of washing and disinfecting fruit and vegetables, importance of fruit and vegetables and the role of students in planning of fruit and vegetable consumption in the family). Then they began to assess and evaluate the amount of fruit and vegetable consumption in their family and encouraged their family members to increase or correct of fruit and vegetable consumption patterns. Questionnaires and checklists were data collecting tools, which were completed 2 times by students: before and 1 month after intervention.   Results: Findings showed that girl students' participation made an increase in their family consumption of fruits and vegetables (P< 0.001).   Conclusion : Based on these findings, the research hypothesis was supported. It means that girl Students' participation can increase fruit and vegetable consumption in the family.